Towards a theory of canonical bestseller: the constitution of a structural model - Muñoz Rico, María; García Rodríguez, Araceli; Cordón García, José Antonio (Revista General de Información y Documentación, 2020)
One of the best known products of the publishing industry is called bestseller, that is, the book that has enjoyed a good reception and sales, reaching, for the most part, the lists of the best sellers. Present in the preferred bookstore sites, virtual platforms and publisher websites, they are easily recognizable works due to their aesthetics and their extension. Their existence is documented since the beginning of the printing press and they represent a genre in themselves. Characterized by its ease of reading, rapid consumption and the use of formulas and narrative strategies that favor its commercialization, its nature is linked more with the economic than with the literary. The academic attention they have received is scarce and, for the most part, critical. They would be the opposite of the concept of canon, understood as the literature par excellence. However, the emergence of information technologies and social networks has led to the formation of a new type of bestseller, characterized both by academic consensus, previously reserved only for the works of the canon, and social consensus, within the framework of a good commercial operation. It is what we have termed as canonical Bestseller. The objective of this article is the study of the terminological and normative foundations of the bestseller, and the proposal of a structural model for the characterization of this new modality of works.